What does it Mean to Make a ‘Joint’ Decision? Unpacking Intra-household Decision Making in Agriculture: Implications for Policy and Practice - Acosta, Mariola; Wessel, Margit van; Bommel, Severine van; Ampaire, Edidah L.; Twyman, Jennifer; Jassogne, Laurence T.P.; Feindt, Peter (Informa UK Limited, 2020)
Strategies to empower women in development contexts frequently address their authority to take decisions within their household, including decisions that are taken jointly by couples. Assessing empowerment in joint decision-making has traditionally followed a dichotomous approach: decisions are either joint or not, with the former associated with women’s empowerment. This paper contributes to a more nuanced understanding of the empowerment effects of joint decision-making, based on case study data from Uganda. We present survey data revealing significant gender differences in perception of decision-making over the adoption of agricultural practices and consumption expenses. Women reported joint decision-making more often than men, who presented themselves more as sole decision makers. We supplement the survey data with an in-depth study in Lodi village, where we reconstruct meanings attached to joint decision-making using focus group discussions, a decision-making game and participant observation. Reported joint decision-making included a range of practices from no conversation among partners to conversations where female spouse’s ideas are considered but the man has the final say. The findings suggest that local interpretations of joint decision-making, in at least this case of a dominantly patriarchal context, can limit its potential for assessing women’s empowerment.